2020
DOI: 10.1542/peds.2020-1023
|View full text |Cite
|
Sign up to set email alerts
|

Well-Child Care Attendance and Risk of Asthma Exacerbations

Abstract: BACKGROUND: Asthma remains a leading cause of hospitalization in US children. Well-child care (WCC) visits are routinely recommended, but how WCC adherence relates to asthma outcomes is poorly described. METHODS: We conducted a retrospective longitudinal cohort study using electronic health records among 5 to 17 year old children residing in Durham County with confirmed asthma and receiving primary care within a single health system, to compare the association between asthma exacerbations and previous WCC expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Notably, all components require regular interactions with the health system to ensure timely evaluation and provision of prescriptions for controller and rescue medications. We and others have previously reported that children who have yearly well‐child visits have decreased risk of asthma exacerbations and related emergency department visits compared with children who do not have regular well‐child visits 11 . Similarly, continuity of care is associated with improved asthma outcomes in children and adolescents 12–16 .…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Notably, all components require regular interactions with the health system to ensure timely evaluation and provision of prescriptions for controller and rescue medications. We and others have previously reported that children who have yearly well‐child visits have decreased risk of asthma exacerbations and related emergency department visits compared with children who do not have regular well‐child visits 11 . Similarly, continuity of care is associated with improved asthma outcomes in children and adolescents 12–16 .…”
Section: Introductionmentioning
confidence: 77%
“…We previously identified 5656 children 5 to <18 years of age who met the criteria for asthma diagnosis, had a Durham County address of residence, and were identified as receiving primary care through the DUHS. 11 Of this initial cohort, 3959 had at least one in‐person healthcare encounter in the year before the start of the COVID‐19 pandemic (Year 1) and were therefore included in the primary analysis. The demographic characteristics of this cohort are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, all components require regular interactions with the health system to ensure timely evaluation and provision of prescriptions for controller and rescue medications. We and others have previously reported that children who have yearly well child visits have decreased risk of asthma exacerbations and related emergency department visits compared with children who do not have regular well child visits 11 . Similarly, continuity of care is associated with improved asthma outcomes in children and adolescents [12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 70%
“…We previously identified 5,656 children 5 to <18 years of age who met the criteria for asthma diagnosis, had a Durham County address of residence, and were identified as receiving primary care through the DUHS 11 . Of this initial cohort, 3,959 had at least one in-person healthcare encounter in the year prior to the start of the COVID-19 pandemic (Year 1) and were therefore included in the primary analysis.…”
Section: Patient Characteristicsmentioning
confidence: 99%